2019
DOI: 10.1155/2019/5050182
|View full text |Cite
|
Sign up to set email alerts
|

Age Matters: Objective Gait Assessment in Early Parkinson’s Disease Using an RGB-D Camera

Abstract: Background. Gait alterations are hallmarks for the diagnosis and follow-up of patients with Parkinson’s disease (PD). In normal conditions, age could affect gait dynamics. Although it is known that objective assessment of gait is a valuable tool for diagnosis and follow-up of patients with PD, only few studies evaluate the effect of aging on the gait pattern of patients with PD. Objective. The purpose of this study was to assess differences in gait dynamics between PD patients and healthy subjects and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It has been well-known that patients with PD demonstrated a smaller step length (32,33), slower gait velocity (34), and more variable gait pattern (20,35,36) than healthy people. However, little is known about the specific differences of gait performance between LPD and RPD.…”
Section: Differences In Gait Performance Between Lpd and Rpdmentioning
confidence: 99%
“…It has been well-known that patients with PD demonstrated a smaller step length (32,33), slower gait velocity (34), and more variable gait pattern (20,35,36) than healthy people. However, little is known about the specific differences of gait performance between LPD and RPD.…”
Section: Differences In Gait Performance Between Lpd and Rpdmentioning
confidence: 99%
“…However, a post-hoc appraisal showed that the pwPD within each stage had a mean age not different from that of the entire HS cohort, except for stage 1 and 1.5. In this regard, a recent article showed that gait-related changes with respect to age appear to be significant in HS but not in pwPD 87 . This limitation is mitigated by the demonstration that gait variability measures remain stable over time and are not influenced by age in HS 88 .…”
Section: Discussionmentioning
confidence: 95%
“…The TUG has a single measurement variable, the execution time, which evaluates general performance based on several tasks, lacking information that detects more slight gait dysfunctions, present in the early stages of PD ( 40 ). Some studies ( 22 , 41 , 42 ) that have compared the effectiveness of TUG with more sophisticated and expensive equipment to identify the decline in gait and mobility in people with PD did not compare their results between stages of PD evolution. Just one study has associated TUG with the characterization of early stages of the disease, and the difficulty in distinguishing them only using the time variable may be one of the reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The most used temporal gait parameters include stride, step duration, and cadence ( 22 ). Most of the studies that sought to investigate gait kinematics parameters correlating them with early detection of PD analyzed their data related to the horizontal axis, such as velocity ( 22 ), stride length ( 59 ), and swing time ( 41 ), through features such as sensors attached to specific parts of the body ( 59 ), pressure platforms ( 60 ) or electromyographic surfaces ( 61 ). These studies could distinguish subjects with PD from control subjects, using more sophisticated resources but without differentiating the stages of disease evolution, particularly the initial ones.…”
Section: Discussionmentioning
confidence: 99%